2022
DOI: 10.1007/s13347-022-00509-3
|View full text |Cite
|
Sign up to set email alerts
|

Can Robots Do Epidemiology? Machine Learning, Causal Inference, and Predicting the Outcomes of Public Health Interventions

Abstract: This paper argues that machine learning (ML) and epidemiology are on collision course over causation. The discipline of epidemiology lays great emphasis on causation, while ML research does not. Some epidemiologists have proposed imposing what amounts to a causal constraint on ML in epidemiology, requiring it either to engage in causal inference or restrict itself to mere projection. We whittle down the issues to the question of whether causal knowledge is necessary for underwriting predictions about the outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Another important issue is technological advances and their association with epidemiology and public health. For example, data analysis mechanisms (through computer tools) in projection and prediction studies have been used systematically, aiming to maximize resources and optimize results in action planning, especially in countries with limited financial resources, such as those in Latin America [ 142 ]. The study by Cabrera et al [ 95 ] demonstrated that machine learning techniques could be successfully employed in dengue prediction models, being an important tool for Latin countries.…”
Section: Considerations and Perspectives For Dengue: Focus On Epidemi...mentioning
confidence: 99%
“…Another important issue is technological advances and their association with epidemiology and public health. For example, data analysis mechanisms (through computer tools) in projection and prediction studies have been used systematically, aiming to maximize resources and optimize results in action planning, especially in countries with limited financial resources, such as those in Latin America [ 142 ]. The study by Cabrera et al [ 95 ] demonstrated that machine learning techniques could be successfully employed in dengue prediction models, being an important tool for Latin countries.…”
Section: Considerations and Perspectives For Dengue: Focus On Epidemi...mentioning
confidence: 99%
“…These instruments have shown some limitations; as already reported in the literature regarding examples of A.I. in the medical field, algorithms may suffer from the poor reproducibility of the data set on which they were built and tested [ 6 , 7 ]. Moreover, although electronic medical records are now widely used, digitalization is not yet complete; this is why adverse events, such as falls, may not be noted, thus escaping A.I.…”
Section: Introductionmentioning
confidence: 99%